Eefects of Product Quality, Service Quality, Price, Familiarity, Reputation, And Application Quality On Shopee Users’ Purchase Intention - Haliza Rahma Alifia; Arif Hartono (CV. Green Publisher Indonesia, 2022)
This study examines the influence of product quality, service quality, price, familiarity, reputation, and application quality on purchase intention by going through Shopee e-commerce to evoke consumers buying interest. Sampling techniques conducted in this study are non-probability purposive sampling by the criteria of respondents were an active student of UII and have shopped at Shopee. The data were collected by using questionnaire based on Likert scale. The total samples obtained in this study were 217 respondents. The data were then analyzed by using Structural Equation Modeling analysis and calculated by using AMOS software. The final results of this study found that positive and significant influence of the product quality, price, familiarity, reputation, and application quality on purchase intention. However, service quality does not have positive effect on purchase intention.